High expression of miR-21 in tissue correlated with the poor survival of patients with esophageal cancer: a pilot study using the meta-analysis - Zhou, Wei; Zhou, Xin; Liu, Jin-qiang; Zhang, Yu-jie; Hong, Liu (Journal of Preventive Medicine And Care, 2016)
Objective: MicroRNAs are involved in the onset, progression and dissemination of esophageal cancer, and they may be useful as prognostic biomarkers. This study aims to evaluate the relation of miR-21 expression and the prognosis of esophageal cancer patients. Methods: In this study, a meta-analysis is performed by searching PubMed, Science Direct databases, and Cochrane Library. Data are extracted from studies evaluating survival of esophageal cancer patients with either high or low miR-21 expression. Pooled hazard ratios (HRs) and 95% confidence intervals (CI) are calculated. Results: A total of 579 cases of esophageal cancer from five studies are involved for this global meta-analysis. The HR of survival of patients with high miR-21 expression is 1.47 (95% CI: 1.12–1.91; p<0.01) as compared with those with low expression. Conclusions: miR-21 may be a predictor for survival of esophageal cancer patients.
Keywords: esophagea cancer; miR-21; survival.